Fixed Points of -Type Quasi-Contractions on Graphs - R. H. Haghi; Sh. Rezapour; N. Shahzad (Abstract and Applied Analysis)
Recently, fixed point theory on graphs has been considered by many authors. In this paper, by combining some ideas in some published papers and introducing -type quasi-contractions, we give some fixed point results for -type quasi-contractions on graphs. The results improve some old results in the literature.